THE ROLE OF SYNERGIC IDEAS IN IMPROVING THE SCIENTIFIC CREATIVE PROCESS - Mamadjonova Marvarid Qurbonnazarovna (European Journal of Humanities and Educational Advancements, 2023)
The article provides a philosophical analysis of the reflection of synergetic ideas in scientific creativity, its features, epistemological aspects. It is based on the importance of synergetics as a method of scientific knowledge in identifying and explaining the multidimensional image of the research process. It is recommended to use its potential in the further development of science and research.